2018
DOI: 10.1029/2018jc013977
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Propagation of Middepth Zonal Currents Associated With Surface Wind Forcing in the Equatorial Indian Ocean

Abstract: The vertical propagation of middepth (200-1,500 m) zonal velocity in the equatorial Indian Ocean (EIO) and its relationship with surface wind forcing are investigated. We focus on semiannual time scales, using in situ mooring observations and an oceanic reanalysis product that can reasonably well reproduce the structure and magnitude of the observed middepth zonal velocity in the EIO. The pronounced semiannual cycle in observed middepth zonal currents indicates a clear upward phase propagation with particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 52 publications
9
28
0
Order By: Relevance
“…Our results are consistent with previous studies (e.g., Luyten & Roemmich, ; Huang, Han, et al, ; Huang, McPhaden, et al, ) that have demonstrated that strong semiannual variations in deep zonal velocities are in part the result of a vertically propagating, first meridional mode Rossby wave. The zonal velocity semiannual signals presented here have been described previously using Argo data (Davis, ) and have been revisited more recently with a focus on the middepth (500–1,500 m) equatorial Indian Ocean (Huang, Han, et al, ; Huang, McPhaden, et al, ). However, we provide a more complete picture of the semiannual variations by including analyses of the meridional velocity (which are novel to the best of our knowledge) and isotherm displacements, both of which indicate the presence of a vertically propagating Rossby wave (Figures ) as well.…”
Section: Summary and Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are consistent with previous studies (e.g., Luyten & Roemmich, ; Huang, Han, et al, ; Huang, McPhaden, et al, ) that have demonstrated that strong semiannual variations in deep zonal velocities are in part the result of a vertically propagating, first meridional mode Rossby wave. The zonal velocity semiannual signals presented here have been described previously using Argo data (Davis, ) and have been revisited more recently with a focus on the middepth (500–1,500 m) equatorial Indian Ocean (Huang, Han, et al, ; Huang, McPhaden, et al, ). However, we provide a more complete picture of the semiannual variations by including analyses of the meridional velocity (which are novel to the best of our knowledge) and isotherm displacements, both of which indicate the presence of a vertically propagating Rossby wave (Figures ) as well.…”
Section: Summary and Discussionsupporting
confidence: 93%
“…West of 65°E, the westward propagation becomes unclear, aligning roughly with the beginning of the region (around 60°–65°E) in the western Indian Ocean where the spatial structure of all three fields is less coherent and amplitudes are smaller (Figure ). The zonal phase speed of the anomalies ( c px ), estimated from the slope of the zonal velocity anomalies in Figure b, is 0.56 m·s −1 , similar to that ( c px = 0.57 m·s −1 ) found by Huang, McPhaden, et al () for their middepth zonal velocities. Calculation of the zonal wavenumber ( k = ω / c px ) yields a zonal wavelength of ~8,800 km, consistent with the larger‐than‐basin‐scale wave suggested by the phase lines in Figure .…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations